Study on the mechanical properties and acoustic emission signal characteristics of freezing pipe - Wang, Tao; Ye, Weiwei; Liu, Liyuan (Frontiers in Earth Science, 2023)
The increase in freezing depth requires thicker, stronger, and colder freezing walls, and various complex factors in deep strata greatly increase the risk of freezing pipe fracture. To address the phenomenon of freezing pipe fracture, this paper designs freezing pipe and joint mechanical performance experiments based on acoustic emission (AE) technology, mainly testing the deformation of freezing steel pipes and composite joints at normal and low temperatures, changes in load bearing capacity, and corresponding AE characteristics of the process. Additionally, the associated AE characteristics throughout the process will be analyzed. The ultimate goal is to establish a discriminative pattern for identifying the critical fracture of freezing pipes based on the analysis of AE signal characteristics in conjunction with mechanical properties. The sensitivity of the AE system under low-temperature conditions and the reliability of the test were tested through pencil lead break experiments, and saltwater noise detection experiments were conducted to prevent noise interference from low-temperature saltwater flow and pipe wall friction in the identification of crucial signals for freezing pipe fracture. This study provides a basis for identifying the deformation mechanics and fracture warning of freezing pipes through dynamic analysis of AE monitoring information.